Tantangan dalam Pembelajaran Berhitung di Kelas Awal dan Cara Mengatasinya - Rachmawati, Wida; Fitri, Dhella Angelina; Saputri, Ramona; Fransiska, Afiona (Lembaga Yasin AlSys, 2023)
The low level of students' understanding in learning mathematics is caused by the assumption held by most students that mathematics is a difficult and boring subject. This diminishes students' motivation to learn, leading to the suggestion that mathematics is a subject to be avoided. This challenge serves as the foundation for the writing of this academic work. Through this research, it is hoped that we can identify the challenges in early math education, particularly in mathematics, and propose efforts to overcome difficulties in learning mathematics, especially in the third grade of Elementary School. This study is conducted using a qualitative method with a descriptive analysis approach. Data collection aims to adjust and obtain information about the factors that make it difficult for students to grasp mathematical concepts. The research results indicate that students' difficulties in learning mathematics consist of three components: difficulty in understanding concepts, difficulty in skills, and difficulty in problem-solving. The factors causing difficulties in learning mathematics originate from both internal and external factors. Based on these factors, efforts that can be made to reduce difficulties in learning mathematics include teaching math in an enjoyable way, using tangible learning media, increasing practice exercises, and establishing cooperation with students' parents.